Unevenly distributed: a systematic review of the literature about socioeconomic inequalities in adult obesity in the United Kingdom - El-Sayed, A; Scarborough, P; Galea, S; El-Sayed, A (BioMed Central, 2012)
BACKGROUND: There is a growing literature documenting socioeconomic inequalities in obesity risk among adults in the UK, with poorer groups suffering higher risk. METHODS: In this systematic review, we summarize and appraise the extant peer-reviewed literature about socioeconomic inequalities in adult obesity risk in the UK published between 1980 and 2010. Only studies featuring empirical assessments of relations between socioeconomic indicators and measures of obesity among adults in the UK were included. RESULTS: A total of 35 articles met inclusion criteria, and were reviewed here. CONCLUSION: Socioeconomic indicators of low socioeconomic position (SEP), including occupational social class of the head-of-household at birth and during childhood, earlier adulthood occupational social class, contemporaneous occupational social class, educational attainment, and area-level deprivation were generally inversely associated with adult obesity risk in the UK. Measures of SEP were more predictive of obesity among women than among men. We outline important methodological limitations to the literature and recommend avenues for future research.